PENGARUH PROFITABILITAS, LEVERAGE, DAN MEDIA EXPOSURE TERHADAP PENGUNGKAPAN EMISI GAS RUMAH KACA - Melinda Farza Musyifa; Nurma Risa (JRAK: Journal of Accounting Research and Computerized Accounting, 2025)
This study aims to determine the influence of profitability, leverage, and media exposure on greenhouse gas emission disclosure. A quantitative approach was used with panel data regression analysis techniques. The research sample is 47 companies in the energy, healthcare, and transportation & logistics sectors listed on the Indonesia Stock Exchange, with the criteria of publishing Annual Reports and Sustainability Reports through internet media and not experiencing losses during the 2021-2023 period. The results of this study show that profitability and media exposure have no effect on the disclosure of greenhouse gas emissions, while leverage has a significant negative effect on the disclosure of greenhouse gas emissions. It is recommended for future researchers, to use other variables and sectors other than those used in this study, so that they can get more optimal research results. Keywords: profitability; leverage; media exposure; greenhouse gas emission disclosure.